Cementing prepad fluid and preparation method thereof
By using a cementable preliminary liquid containing components such as suspension stabilizers, active gelling materials, etc. during the drilling process, the problem of difficulty in curing residual drilling fluid in irregular well sections is solved, and efficient cementing and improving the quality of annular cementing is achieved.
Patent Information
- Application Number
- CN202311262846.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
During the drilling process, especially for irregular wellbore sections, such as S-shaped well sections, big-bend well sections, candied haws sections, etc., conventional cementing operations cannot effectively drive away the residual drilling fluid, resulting in poor cementing quality at the two interfaces, affecting the enclosure and safety of the well section.
A cementable preliminary liquid is used, and its raw materials include water, suspension stabilizers, active gelling materials, diluents, water-reducing agents and weighting agents. Through the composite synergistic action, the preliminary fluid can undergo cementing and solidification reaction with the residual cement slurry and drilling fluid, improving the annular cementing quality.
Efficient replacement and cementing of irregular well sections are achieved, the quality of annular cementing is improved, the negative impact of activators on the performance of cement slurry is avoided, construction safety is ensured, and costs are reduced.
Smart Images

Figure CN119709143A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of drilling, and in particular to a cementable pre-pad fluid and a preparation method thereof. Background Art
[0002] Cementing of oil and gas wells refers to the process of pumping cement slurry into the annulus between the casing and the well wall during the completion operation, and allowing the cement slurry to solidify and solidify within a certain period of time to form a complete cement ring with good interlayer isolation ability. The cementing interface includes the contact surface of the casing-cement ring and the cement ring-well wall. The interface bonding performance is mainly affected by many factors such as the roughness and cleanliness of the casing, the physical and chemical properties of the well wall rock, the performance of the pre-fluid, the performance of the cement slurry, the displacement efficiency of the pre-fluid and cement slurry on the drilling fluid, and the removal effect of the drilling fluid filter cake and oil film at the interface. Under certain special well conditions, some irregular wellbore sections often appear, such as S-shaped sections, big belly sections, and candied haws sections. These sections are prone to residual drilling fluid, and conventional cementing operations cannot displace them well. In addition, they cannot solidify and bond by themselves, which affects the bonding quality of the two interfaces and buries hidden dangers for oil, gas and water channeling in the annulus.
[0003] The problem of cementation between the two interfaces has become a difficult problem to be solved in the field of cementing engineering. Domestic and foreign scholars have conducted many useful explorations, such as MTA, multifunctional drilling fluid, MTC and curable pre-fluid technology, and have also achieved certain research results. Combining the implementation methods and technical principles of the above technologies, it is not difficult to find that these methods are fundamentally to add a curing material (usually BFS) and a curing aid (strong activator) to the drilling fluid and pre-fluid, and to activate a small amount of curable components in the curing material or drilling fluid to consolidate the filter cake, thereby achieving overall curing and cementation of the two interfaces of cementing. However, when a large amount of activator is added to the pre-fluid, on the one hand, the rheological properties of the pre-fluid are difficult to adjust, and it is difficult to meet the on-site displacement requirements and ensure the displacement efficiency. On the other hand, a large amount of activator is easy to affect the performance of cement slurry and affect construction safety. In addition, the commonly used activators are highly corrosive strong alkalis, which are hazardous chemicals and are subject to great restrictions in practical applications. Summary of the invention
[0004] The present application provides a cementable pre-fluid and a preparation method thereof, which can avoid the problem of adding a large amount of activator into the pre-fluid, which causes the rheological properties of the pre-fluid to be difficult to adjust, making it difficult to meet on-site replacement requirements, affecting cement slurry performance, and affecting construction safety.
[0005] This application adopts the following technical solutions:
[0006] The present application provides a cementable pre-fluid, the raw materials of which include the following components in parts by weight: 100 parts by weight of water, 2 to 3.5 parts by weight of a suspension stabilizer, 40 to 65 parts by weight of an active cementitious material, 0 to 4 parts by weight of a diluent, 3 to 4 parts by weight of a fluid loss reducer, and 0 to 160 parts by weight of a weighting agent.
[0007] Furthermore, the raw material composition of the active cementitious material includes, by weight: 5 to 18 parts by weight of red mud, 20 to 50 parts by weight of ultrafine slag, 5 to 15 parts by weight of fly ash, 5 to 15 parts by weight of kaolin, 0.5 to 1 part by weight of desulfurized gypsum, 0.025 to 0.1 parts by weight of chitin polymer, 0.025 to 0.1 parts by weight of chitosan polymer and 0.05 to 0.10 parts by weight of a terpolymer of 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and vinyl carbamate.
[0008] Furthermore, the suspension stabilizer includes a terpolymer of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and N-vinyl pyrrolidone, xanthan gum, and carboxyethyl cellulose, and the mass ratio of the terpolymer of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and N-vinyl pyrrolidone to xanthan gum and carboxyethyl cellulose is 85:10:5.
[0009] Furthermore, the diluent includes the following components in percentage by mass: 40% sodium lignin sulfonate, 10% sulfonated tannin, 10% sodium dodecylbenzene sulfonate, and 40% water.
[0010] Furthermore, the fluid loss additive includes a terpolymer of 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and itaconic acid.
[0011] Further, the weighting agent includes barite.
[0012] The present application also provides a method for preparing the above-mentioned cementable pre-pad liquid, comprising the following steps: adding a suspension stabilizer to water according to the weight proportion of each component, performing a first stirring to obtain a first mixed liquid; adding a diluent and a fluid loss reducer to the first mixed liquid, performing a second stirring to obtain a second mixed liquid; adding an active gelling material and a weighting agent to the second mixed liquid, performing a third stirring to obtain a cementable pre-pad liquid.
[0013] Furthermore, the first stirring time is 5 to 10 minutes, and the rotation speed is 3800 to 4200 rpm.
[0014] Furthermore, the second stirring time is 5 to 10 minutes, and the rotation speed is 3800 to 4200 rpm.
[0015] Furthermore, the third stirring time is 8 to 15 minutes, and the rotation speed is 3800 to 4200 rpm.
[0016] Compared with the prior art, this application has the following beneficial effects:
[0017] In the cementable pre-fluid provided in the embodiment of the present application, the active cementitious material is formed by compounding inorganic materials and organic materials, and there is a composite synergistic effect between the various components, and can undergo a cementing and curing reaction with the cement slurry and drilling fluid remaining at the cementing interface to improve the annular cementation quality; the suspension stabilizer is hydrated when it meets water to form a network cross-linked structure with a certain structure, which has a certain supporting effect and can prevent the sedimentation of solid phase particles in the pre-fluid; the diluent uses the mutual repulsion of like charges to inhibit the aggregation of solid phase particles, thereby ensuring the fluidity of the working fluid, and its main function is to improve the rheological properties of the mixed slurry and reduce the degree of contact pollution between the drilling fluid and the cement slurry; the fluid loss reducer prevents the aggregation of solid phase particles through adsorption and hydration groups, which can maintain a moderate distribution of particles and reduce the water loss of the pre-fluid; the weighting agent mainly functions to balance the formation pressure and achieve effective density displacement of the drilling fluid.
[0018] The pre-fluid of the present application has four major characteristics, namely, improved annular space cementation quality, isolation, efficient displacement, and low cost, through the composite synergistic effect of the above materials: (1) No activator is required, and the residual cementing fluid in irregular well sections can be effectively cemented and solidified, and the annular space cementation quality is significantly improved; (2) The system has good compatibility, which can effectively isolate the drilling fluid and cement slurry at the interface to prevent the mixed slurry residue from contaminating the cementing interface; (3) It has good rheological properties and stability, and can produce buoyancy on the drilling fluid through positive density difference, which is beneficial to improve the displacement efficiency; (4) Using energy waste and biomass waste as source materials can transfer waste from the environment, with low cost, closed material cycle, and promotion of circular economy. The pre-fluid of the present application can avoid the problem of adding a large amount of activator into the pre-fluid, which makes it difficult to adjust the rheological properties of the pre-fluid, meet the on-site displacement requirements, affect the performance of the cement slurry, and affect the construction safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The chemical structures of chitin and chitosan are shown below;
[0020] Figure 2 This is the thickening curve of 1# cement slurry;
[0021] Figure 3 This is the thickening curve of the 2# field drilling fluid, pre-fluid and cement slurry in the ratio of 20:10:70. DETAILED DESCRIPTION
[0022] The technical methods in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0023] An embodiment of the present application provides a cementable pre-fluid, the raw materials of which include the following components in parts by weight: 100 parts by weight of water, 2 to 3.5 parts by weight of a suspension stabilizer, 40 to 65 parts by weight of an active cementitious material, 0 to 4 parts by weight of a diluent, 3 to 4 parts by weight of a fluid loss reducer, and 0 to 160 parts by weight of a weighting agent.
[0024] Among them, the amount of suspension stabilizer is 2, 3, 3.5 parts by weight. The suspension stabilizer is a ternary polymer of 2-acrylamide-2-methylpropane sulfonic acid (AMPS), N, N dimethylacrylamide (DMAA), N-vinyl pyrrolidone (NVP) (AMPS-DMAA-NVP ternary polymer) and xanthan gum and carboxyethyl cellulose, that is, the suspension stabilizer is a composition of the above three components. The mass ratio of the ternary polymer of 2-acrylamide-2-methylpropane sulfonic acid, N, N dimethylacrylamide, N-vinyl pyrrolidone to xanthan gum and carboxyethyl cellulose can be 85:10:5. In the suspension stabilizer, each component together forms a certain network structure or forms a network structure through hydration, adsorption, etc., which has a certain supporting effect and can prevent the sedimentation of solid phase particles in the pre-liquid.
[0025] The dosage of active cementitious material is 40, 50, 65, etc. parts by weight. In terms of parts by weight, the inorganic material composition of active cementitious material includes: 5-18 parts by weight of red mud, 20-50 parts by weight of ultrafine slag, 5-15 parts by weight of fly ash, 5-15 parts by weight of metakaolin, 0.5-1 parts by weight of desulfurized gypsum; the organic material composition includes: 0.025-0.1 parts by weight of chitin polymer, 0.025-0.1 parts by weight of chitosan polymer and 0.05-0.10 parts by weight of terpolymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), N,N-dimethylacrylamide (DMAA), and vinyl carbamic acid tert-butyl ester.
[0026] The amount of red mud used is 5, 10, 18 parts by weight. The specific surface area of red mud is greater than 170m 2 / kg, sintering temperature is 1100 degrees, and holding time is 15min. Red mud is alkaline solid waste. The chemical composition of red mud includes CaO (2-8%), Al2O3 (10-20%), Fe2O3 (30-60%), SiO2 (3-20%), TiO2 (trace ~ 10%) and Na2O (2-10%).
[0027] The dosage of ultrafine slag is 20, 30, 50 parts by weight. The specific surface area of slag is greater than 550m 2 / kg. Slag is a silicon-aluminum solid waste. The chemical composition of slag includes: SiO2 (27-42%), CaO (30-50%), Al2O3 (5-33%), MgO (0-21%). It also includes a small amount of CaS, MnO, FeO, TiO2, etc.
[0028] The amount of fly ash used is 5, 10, 15 parts by weight. The specific surface area of fly ash is greater than 600m 2 / kg, and the sintering temperature is as high as 1400 degrees. Fly ash is a silicon-alumina solid waste. The fly ash produced is mainly regular spherical particles, and the surface of the micro-beads is relatively smooth. The chemical composition of fly ash includes SiO2, Al2O3, and Fe2O3, and the total amount of the three is about 70%. It also includes other alkaline earth metal oxides, and the content is low.
[0029] The amount of metakaolin used is 5, 10, 15 parts by weight. The specific surface area of metakaolin is greater than 500m 2 / kg, sintering temperature is 900-1000 degrees, sintering time is 6-8h. Metakaolin is a silicon-aluminum solid waste. The chemical composition of metakaolin includes SiO2, Al2O3, and Fe2O3, the total amount of which is about 90
[0030] %. Other alkaline earth metal oxides are also included, and the content is low.
[0031] The dosage of desulfurized gypsum is 0.5, 0.8, 1 and other parts by weight. Desulfurized gypsum is a sulfate solid waste. The chemical composition of desulfurized gypsum includes CaSO4·2H2O, which accounts for more than 90% of the solid matter. It also includes other impurities such as calcium carbonate, calcium sulfite, silicon dioxide, and metal compounds.
[0032] The dosage of chitosan polymer is 0.025, 0.05, 0.1 and other parts by weight. Chitosan is a binary linear copolymer in which N-acetylglucosamine and N-glucosamine units are randomly distributed on the biopolymer chain. The dosage of chitosan polymer is 0.025, 0.05, 0.1 and other parts by weight. The difference between chitosan and chitosan lies in the degree of acetylation. When the acetylation degree of the product is less than 50%, it is chitosan. Both chitosan and chitosan are extracted from biomass waste. The chemical structures of chitosan and chitosan are as follows: Figure 1 shown.
[0033] The amount of the terpolymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), N,N-dimethylacrylamide (DMAA), and vinyl carbamate tert-butyl ester is 0.05, 0.08, 0.10, etc. parts by weight. The chemical structure of the terpolymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) / N,N-dimethylacrylamide (DMAA) / vinyl carbamate tert-butyl ester consists of the sulfonic acid group and amide group in the AMPS monomer, the amide group in the DMAA monomer, and the carboxylic acid group in the vinyl carbamate monomer, thereby forming a bridging structure of the terpolymer.
[0034] In active gelling materials, each component has a significant composite synergistic effect under reasonable composition ratio conditions. In addition, due to the different particle sizes of inorganic materials, effective filling of large and small particles can increase the stacking rate of the system and have a certain tight stacking effect.
[0035] Among them, ultrafine slag, fly ash and kaolin contain a large amount of silicon oxide, calcium oxide, aluminum oxide, iron oxide and other substances. These substances can react with calcium hydroxide in the cement slurry filtrate to form a hydraulic gel. This type of gel material has good adhesion, thereby improving the interfacial bonding strength.
[0036] The active substances in red mud and desulfurized gypsum can quickly participate in the reaction. Red mud is alkaline, and desulfurized gypsum provides sulfate. In an alkaline and sulfate environment, the silicon and aluminum substances in ultrafine slag, fly ash, kaolin and red mud are dissolved, causing the hydration degree of ultrafine slag, fly ash, kaolin and red mud to proceed in the direction of a reaction with a higher degree of polymerization. A large amount of gel and calcium aluminate hydration products such as CSH are increased, which reduces the porosity of the cementitious material matrix and forms a dense structure, thereby improving its mechanical properties.
[0037] The terpolymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) / N,N-dimethylacrylamide (DMAA) / tert-butyl vinyl carbamate is a bridged polymer. The high molecular weight of the polymer gives it good strength and chemical resistance, and it can maintain structural integrity for a long time at high temperatures. The polymer can absorb a large amount of water molecules, promote the formation of gels such as CSH and ettringite-type hydration products, thereby ensuring strength development.
[0038] The hydroxyl and amide groups in the structure of chitin polymers and chitosan polymers can form hydrogen bonds with gels such as CSH and ettringite-like hydration products, thereby further improving the mechanical and microstructural properties of the gelling system.
[0039] The diluent includes the following components in mass percentage: 40% sodium lignin sulfonate, 10% sulfonated tannin, 10% sodium dodecylbenzene sulfonate, and 40% water. In the diluent, sulfonate is easily soluble in water to generate anions, which continuously aggregate on the surface of solid particles, making the two carry the same charge, and utilizing the mutual repulsion of like charges to inhibit the aggregation of solid phase particles, thereby ensuring the fluidity of the working fluid, and mainly improving the rheological properties of the slurry and reducing the degree of pollution caused by contact between drilling fluid and cement slurry.
[0040] The fluid loss reducer is a ternary polymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), N,N-dimethylacrylamide (DMAA), and itaconic acid (IA). The fluid loss reducer prevents the aggregation of solid phase particles through adsorption and hydration groups, which can maintain the appropriate distribution of particles and reduce the water loss of the pre-fluid.
[0041] The weighting agent is barite. The density of barite is 4.3-4.6 g / cm 3 The particle size of barite is required to be around 300 mesh. The price of barite is low. The finer barite powder is better dispersed in the pre-fluid.
[0042] The present application adds active cementitious materials to the pre-fluid and adds a small amount of organic materials to the cementitious materials, without the need to specially add other activators, to achieve the cementation and curing of the pre-fluid, improve the cementation quality of the two interfaces, and solve the problem that a large amount of activators affect construction safety. The active cementitious materials in the pre-fluid are formed by compounding inorganic materials and organic materials. There is a composite synergistic effect between the components, and they can react with the cement slurry and drilling fluid remaining on the cementing interface to undergo a cementation and curing reaction. The annular cementation quality is significantly improved, solving the problem of poor displacement efficiency in irregular wellbore sections, and easy retention of drilling fluid and pre-fluid, resulting in poor cementation quality at the cement annulus interface. The pre-fluid of the present application can not only isolate the drilling fluid and cement slurry to prevent mixed slurry contamination, but also has the ability to solidify and bond, improving the interface sealing quality.
[0043] The embodiment of the present application also provides a method for preparing the above-mentioned bindable pre-pad liquid, comprising the following steps:
[0044] (1) Add a suspension stabilizer to water according to the weight proportions of each component, and perform a first stirring to obtain a first mixed solution.
[0045] In the above steps, the first stirring time is 5 to 10 minutes, such as 5, 7, 10 minutes, etc., and the rotation speed is 3800 to 4200 rpm, such as 3800, 4000, 4200 rpm, etc.
[0046] (2) Adding a diluent and a fluid loss reducer to the first mixed solution, performing a second stirring, and obtaining a second mixed solution.
[0047] In the above steps, the second stirring time is 5 to 10 minutes, such as 5, 8, 10 minutes, etc., and the rotation speed is 3800 to 4200 rpm, such as 3800, 4000, 4200 rpm, etc.
[0048] (3) Adding active gelling material and weighting agent to the second mixed liquid, performing a third stirring, and obtaining a bindable pre-liquid.
[0049] In the above steps, the third stirring time is 8 to 15 minutes, such as 8, 10, 15 minutes, etc., and the rotation speed is 3800 to 4200 rpm, such as 3800, 4000, 4200 rpm, etc.
[0050] The present invention can achieve the cementation and curing of the pre-fluid by adding an active gelling material to the pre-fluid and adding a small amount of organic material to the gelling material without adding other activators, thereby improving the cementation quality of the two interfaces. In addition, the raw materials of the present invention are low in cost and easy to obtain, and the product performance is excellent.
[0051] The following is a detailed description with reference to specific embodiments:
[0052] Example 1
[0053] Add 2.55g AMPS-DMAA-NVP ternary polymer, 0.3g xanthan gum, 0.15g carboxyethyl cellulose to 100g water, stir at 4000rpm for 5min, dissolve for 30min to obtain the first mixed solution. Then add 3g fluid loss reducer to the first mixed solution, stir at 4000rpm for 5min, and evenly dissolve to obtain the second mixed solution. Then add 5g red mud, 20g ultrafine slag, 5g fly ash, 10g metakaolin, 1g desulfurized gypsum, 0.1g chitin polymer, 0.025g chitosan polymer and 0.05g 2-acrylamide-2-methylpropanesulfonic acid-N, N dimethylacrylamide-vinyl carbamic acid tert-butyl ester ternary polymer to the second mixed solution, stir at 4000rpm for 8min, and evenly stir to obtain a cementable pre-fluid.
[0054] Example 2
[0055] Add 2.13g AMPS-DMAA-NVP ternary polymer, 0.25g xanthan gum, 0.125g carboxyethyl cellulose to 100g water, stir at 4000rpm for 5min, dissolve for 30min to obtain the first mixed solution. Then add 3g fluid loss agent to the first mixed solution, stir at 4000rpm for 5min, and evenly dissolve to obtain the second mixed solution. Then add 5g red mud, 40g ultrafine slag, 8g fly ash, 10g metakaolin, 0.5g desulfurized gypsum, 0.1g chitin polymer, 0.025g chitosan polymer, 0.05g 2-acrylamide-2-methylpropanesulfonic acid-N, N dimethylacrylamide-vinyl carbamic acid tert-butyl ester ternary polymer and 35g barite to the second mixed solution, stir at 4000rpm for 10min, and evenly stir to obtain a cementable pre-fluid.
[0056] Example 3
[0057] Add 2.13g AMPS-DMAA-NVP ternary polymer, 0.25g xanthan gum, 0.125g carboxyethyl cellulose to 100g water, stir at a speed of 4000rpm for 5min, dissolve for 30min, and obtain a first mixed solution. Then add 3g of fluid loss reducer to the first mixed solution, stir at a speed of 4000rpm for 5min, and evenly dissolve to obtain a second mixed solution. Then add 5g red mud, 40g ultrafine slag, 8g fly ash, 10g metakaolin, 0.5g desulfurized gypsum, 0.1g chitin polymer, 0.05g chitosan polymer, 0.05g 2-acrylamide-2-methylpropanesulfonic acid-N, N dimethylacrylamide-vinyl carbamic acid tert-butyl ester ternary polymer and 60g barite to the second mixed solution, stir at a speed of 4000rpm for 10min, and stir evenly to obtain a cementable pre-fluid.
[0058] Example 4
[0059] 2.55 g of AMPS-DMAA-NVP ternary polymer, 0.3 g of xanthan gum, and 0.15 g of carboxyethyl cellulose were added to 100 g of water, stirred at a rotation speed of 4000 rpm for 5 min, and dissolved for 30 min to obtain a first mixed solution. Then, 4 g of fluid loss reducer, 0.8 g of sodium lignin sulfonate, 0.2 g of sulfonated tannin, 0.2 g of sodium dodecylbenzene sulfonate, and 0.8 g of water were added to the first mixed solution, stirred at a rotation speed of 4000 rpm for 5 min, and uniformly dissolved to obtain a second mixed solution. Then, 5 g of red mud, 40 g of ultrafine slag, 8 g of fly ash, 10 g of kaolin, 0.5 g of desulfurized gypsum, 0.1 g of chitin polymer, 0.05 g of chitosan polymer, 0.05 g of 2-acrylamide-2-methylpropanesulfonic acid-N,N-dimethylacrylamide-vinylcarbamic acid tert-butyl ester terpolymer and 115 g of barite were added to the second mixed liquid, and the mixture was stirred at 4000 rpm for 10 min. After stirring evenly, a cementable pre-liquid was obtained.
[0060] Example 5
[0061] 2.55 g of AMPS-DMAA-NVP ternary polymer, 0.3 g of xanthan gum, and 0.15 g of carboxyethyl cellulose were added to 100 g of water, stirred at a rotation speed of 4000 rpm for 5 min, and dissolved for 30 min to obtain a first mixed solution. Then, 4 g of fluid loss reducer, 0.8 g of sodium lignin sulfonate, 0.2 g of sulfonated tannin, 0.2 g of sodium dodecylbenzene sulfonate, and 0.8 g of water were added to the first mixed solution, stirred at a rotation speed of 4000 rpm for 5 min, and uniformly dissolved to obtain a second mixed solution. Then, 5 g of red mud, 40 g of ultrafine slag, 8 g of fly ash, 10 g of kaolin, 0.5 g of desulfurized gypsum, 0.1 g of chitin polymer, 0.05 g of chitosan polymer, 0.05 g of 2-acrylamide-2-methylpropanesulfonic acid-N,N-dimethylacrylamide-vinylcarbamic acid tert-butyl ester terpolymer and 160 g of barite were added to the second mixed liquid, and the mixture was stirred at 4000 rpm for 10 min. After stirring evenly, a bindable pre-liquid was obtained.
[0062] Comparative Example 1
[0063] 2.13g AMPS-DMAA-NVP ternary polymer, 0.25g xanthan gum, and 0.125g carboxyethyl cellulose were added to 100g water, stirred at a speed of 4000rpm for 5min, and dissolved for 30min to obtain a first mixed solution. Then 3g of fluid loss reducer was added to the first mixed solution, stirred at a speed of 4000rpm for 5min, and uniformly dissolved to obtain a second mixed solution. Then 85g of barite was added to the second mixed solution, stirred at a speed of 4000rpm for 10min, and stirred evenly to obtain the comparison pre-fluid provided in the present embodiment.
[0064] Comparative Example 2
[0065] Add 2.13g AMPS-DMAA-NVP ternary polymer, 0.25g xanthan gum, 0.125g carboxyethyl cellulose to 100g water, stir at 4000rpm for 5min, dissolve for 30min to obtain the first mixed solution. Then add 3g fluid loss reducer to the first mixed solution, stir at 4000rpm for 5min, and evenly dissolve to obtain the second mixed solution. Then add 5g red mud, 40g ultrafine slag, 8g fly ash, 10g metakaolin, 0.5g desulfurized gypsum and 35g barite to the second mixed solution, stir at 4000rpm for 10min, and evenly stir to obtain a cementable pre-fluid.
[0066] Test Example 1
[0067] The performance test of the pre-pad fluid was carried out in accordance with the Chinese national standard GB / T 19139-2012 "Test Methods for Oil Well Cement" and the petroleum and natural gas industry standard SY / T 5374-2000 "Methods for Using Cement Pre-pad Fluids for Oil and Gas Wells". The specific tests were conducted on the rheological properties and stability of the cementing pre-pad fluid. The results are shown in Table 1.
[0068] Table 1 Rheological properties and stability of the pre-pad solution prepared in Examples 1 to 5 (70°C)
[0069]
[0070] It can be seen from Table 1 that the rheological parameters of the cementable pre-pad fluid prepared in this application satisfy that n is greater than 0.6 and the consistency coefficient k is less than 0.6 Pa.s n , the density difference is less than 0.03g / cm 3 The cementable pre-fluid has good stability and rheological properties and meets the requirements of safe pumping.
[0071] Test Example 2
[0072] The compressive strength of the cementitious pre-fill liquid and nano-low-density cement slurry mixed in different proportions and cured in a 70°C water bath for 3 days was tested. The results are shown in Table 2.
[0073] The formula of nano low-density cement slurry is as follows: 1.50g / cm 3 Nano low-density cement slurry system: G-grade cement 100+lightening reinforcing material nano-based composite 45+fluid loss reducer 4+retarder 0.2+dispersant 1.2+water 110+defoaming agent 0.1.
[0074] Table 2 Compressive strength of mixed slurry prepared from pre-drip fluids of Examples 1 to 5 and Comparative Examples 1 to 2 and different amounts of cement slurry
[0075]
[0076] The cementitious pre-fluid itself will not solidify to form a solid body. After contacting with cement slurry, the strength of the slurry increases with the increase of cement slurry proportion. The density is 1.5g / cm 3 Compared with the comparative example 1, the cementable pre-fluid can increase the slurry strength from 0MPa to 4.5MPa after mixing with the nano low-density cement slurry at a ratio of 9:1, the slurry strength can be increased from 0MPa to 6.5MPa after mixing at a ratio of 8:2, and the slurry strength can be increased from 0.7MPa to 7.6MPa after mixing at a ratio of 7:3. Compared with the comparative example 2, it can be seen that the strength of the slurry can be further improved after adding the organic cementitious material to the cementitious material. This shows that the pre-fluid remaining in the irregular wellbore section such as the big belly well can react with the subsequent residual cement slurry to hydrate, so as to improve the bonding strength between the cement stone and the interface and improve the interlayer sealing quality.
[0077] Test Example 3
[0078] Test Example 2 can bind pre-pad liquid with 1.5 g / cm 3 Nano low density cement slurry and on-site 1.2g / cm 3 The compressive strength of potassium salt polymer drilling fluid mixed in different proportions and cured in a 70℃ water bath for 3 days is shown in Table 1.
[0079] Table 3 Compression strength of the three mixtures (70℃×72h)
[0080] Serial number Cement slurry Pre-fluid Drilling Fluid Compressive strength MPa 1 1 1 1 0 2 1 2 1 0 3 2 2 1 3.9
[0081] As the proportion of pre-fluid or cement slurry increases, and as the percentage of curable components increases, the compressive strength value of the mixed solidified body also increases. When cement slurry: pre-fluid: drilling fluid = 2:2:1, the compressive strength can reach 3.9MPa, achieving the overall curing and bonding of the three mixed fluids, so that the interface of the casing wall-cement ring-formation can be well consolidated together. This system effectively improves the bonding quality of the cementing interface, and ultimately achieves the purpose of improving the cementing quality.
[0082] Test Example 4
[0083] The interface enhancement effect of the cementable pre-fluid was evaluated by using an artificial core to simulate the formation. The test method is as follows: a cylindrical simulated core with a diameter of 7 cm and a height of 12 cm was soaked in the cementable pre-fluid for 10 minutes, taken out, and after no liquid drops fell on the surface of the core, it was placed in the center of a steel pipe with an inner diameter of 32 mm and a height of 200 mm to simulate the cementing annulus; cement slurry was poured into the annulus and the temperature was raised for curing. During the test, the maximum pressure value when the core and the cement sheath were relatively displaced was read, and the annulus interface cementation strength was calculated in combination with the lateral area of the core. The results are shown in Table 4.
[0084] Table 4 Interface bonding strength between pre-pad fluid and cement slurry prepared in Examples 1 to 5 and Comparative Examples 1 to 2
[0085]
[0086]
[0087] Compared with comparative example 1, the interface bonding strength of the cementable pre-fluid with the nanometer low-density cement slurry is increased from 0.4MPa to 1.0MPa, and compared with comparative example 2, the interface bonding strength of the cementable pre-fluid with the nanometer low-density cement slurry is increased from 0.7MPa to 1.0MPa. The reason for this is that the active cementitious material is formed by compounding inorganic materials and organic materials, and there is a composite synergistic effect between the components, which can react with the cement slurry remaining at the interface to form a solidified body with a certain strength that can consolidate the well wall, thereby improving the bonding quality of the cement and the well wall.
[0088] Test Example 5
[0089] The compatibility of the cementable pad fluid of Example 2 with the on-site drilling fluid and cement slurry was tested, and the results are shown in Tables 5 and 6. The method is as follows: the cementable pad fluid and the drilling fluid / cement slurry are mixed in different volume ratios.
[0090] Table 5 Rheological compatibility of drilling fluid and cementable pre-pad fluid (70℃) Table 6 Compatibility of cement slurry and cementitious pre-pad fluid (70℃)
[0091]
[0092]
[0093] The experimental results show that the fluidity of the mixed slurry is greater than 18cm. The cementing pre-fluid can effectively dilute the drilling fluid. There is no obvious thickening phenomenon after mixing with the on-site drilling fluid and cement slurry. It has good rheological compatibility, can improve the displacement efficiency, and prevent the mixed slurry pollution between cement slurry and drilling fluid.
[0094] The compatibility of the cementable pre-pad fluid with the nano-low-density cement slurry and the on-site drilling fluid in Example 2 was tested. The results are shown in Tables 7 and Figure 2-3 shown.
[0095] Table 7 Compatibility test of pre-fluid with drilling fluid and cement slurry thickening (71℃×45MPa×45min)
[0096] Serial number Cement slurry Drilling Fluid Pre-fluid Thickening time 1 100 — — 220min 2 70 20 10 More than 300min 3 70 — 30 More than 300min 4 90 — 10 More than 300min
[0097] The experimental results show that: by comparison, it is found that the thickening time of the slurry is within the safe range. As can be seen from the figure, the thickening curve of the slurry is good. Under high temperature and high pressure conditions, the viscosity of the slurry has no obvious fluctuations, indicating that the pre-fluid has good thickening compatibility with cement slurry and drilling fluid, and meets the requirements of on-site safety construction.
[0098] In the cementable pre-fluid provided in the embodiment of the present application, the active cementitious material is formed by compounding inorganic materials and organic materials, and there is a composite synergistic effect between the various components, and can undergo a cementing and curing reaction with the cement slurry and drilling fluid remaining at the cementing interface to improve the annular cementation quality; the suspension stabilizer is hydrated when it meets water to form a network cross-linked structure with a certain structure, which has a certain supporting effect and can prevent the sedimentation of solid phase particles in the pre-fluid; the diluent uses the mutual repulsion of like charges to inhibit the aggregation of solid phase particles, thereby ensuring the fluidity of the working fluid, and its main function is to improve the rheological properties of the mixed slurry and reduce the degree of contact pollution between the drilling fluid and the cement slurry; the fluid loss reducer prevents the aggregation of solid phase particles through adsorption and hydration groups, which can maintain a moderate distribution of particles and reduce the water loss of the pre-fluid; the weighting agent mainly functions to balance the formation pressure and achieve effective density displacement of the drilling fluid. Through the synergistic effect of the above materials, the pre-fluid has four major characteristics, namely, improved annular cementation quality, isolation, efficient displacement, and low cost: (1) No activator is required, and the residual cementing fluid in irregular well sections can be effectively cemented and solidified, with significant improvement in annular cementation quality; (2) The system has good compatibility and can effectively isolate the drilling fluid and cement slurry at the interface to prevent the mixed slurry residue from contaminating the cementing interface; (3) It has good rheological properties and stability, and can generate buoyancy on the drilling fluid through positive density difference, which is beneficial to improving displacement efficiency; (4) Using energy waste and biomass waste as source materials can transfer waste from the environment, with low cost, close the material cycle, and promote the circular economy.
[0099] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and the scope of protection required by the present application is defined by the attached claims, description and their equivalents.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A cementable pre-pad fluid, characterized in that: The raw materials include the following components in parts by weight: 100 parts by weight of water, 2-3.5 parts by weight of a suspension stabilizer, 40-65 parts by weight of an active gelling material, 0-4 parts by weight of a diluent, 3-4 parts by weight of a fluid loss reducer, and 0-160 parts by weight of a weighting agent.
2. A cementable pre-pad according to claim 1, characterized in that: The raw material composition of the active gelling material includes, by weight: 5-18 parts by weight of red mud, 20-50 parts by weight of ultrafine slag, 5-15 parts by weight of fly ash, 5-15 parts by weight of metakaolin, 0.5-1 parts by weight of desulfurized gypsum, 0.025-0.1 parts by weight of chitin polymer, 0.025-0.1 parts by weight of chitosan polymer and 0.05-0.10 parts by weight of a terpolymer of 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and tert-butyl vinylcarbamate.
3. A cementable pre-pad according to claim 1, characterized in that: The suspension stabilizer includes a ternary polymer of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and N-vinyl pyrrolidone, xanthan gum, and carboxyethyl cellulose, and the mass ratio of the ternary polymer of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and N-vinyl pyrrolidone to xanthan gum and carboxyethyl cellulose is 85:10:
5.
4. A cementable pre-pad according to claim 1, characterized in that: The diluent comprises the following components in the following mass percentages: 40% sodium lignin sulfonate, 10% sulfonated tannin, 10% sodium dodecylbenzene sulfonate and 40% water.
5. A cementable pre-pad according to claim 1, characterized in that: The fluid loss reducer comprises a terpolymer of 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and itaconic acid.
6. A cementable pre-pad according to claim 1, characterized in that: The weighting agent includes barite.
7. A method for preparing a bindable prepad according to any one of claims 1 to 6, characterized in that: The following steps are involved: Adding a suspension stabilizer to water according to the weight proportions of each component, performing a first stirring, and obtaining a first mixed solution; Adding a diluent and a fluid loss reducer to the first mixed solution, and performing a second stirring to obtain a second mixed solution; Add active gelling material and weighting agent to the second mixed liquid, and perform a third stirring to obtain the bindable pre-pad liquid.
8. The method for preparing a bindable prepad according to claim 7, characterized in that: The first stirring time is 5 to 10 minutes, and the rotation speed is 3800 to 4200 rpm.
9. The method for preparing a bindable prepad according to claim 7, characterized in that: The second stirring time is 5 to 10 minutes, and the rotation speed is 3800 to 4200 rpm.
10. The method for preparing a bindable prepad according to claim 7, characterized in that: The third stirring time is 8 to 15 minutes, and the rotation speed is 3800 to 4200 rpm.